Analisis Pedagogi Kristen Terhadap Perkembangan Spiritualitas Anak Pada Keluarga Broken Home - Attu, Juliati; Eting, Srinengsih; Indri, Indrianingsy (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2023)
The family is the smallest social unit that provides the foundation for children's development and the formation of children's character and personality. The family is also considered the first and main source of education for children, including religious education. But sometimes, the education children get in families is less than optimal, such as in families with broken homes. Christian education that is less than optimal for children can affect their spiritual development; as a result, they become fragile in facing various pressures of life. This study aims to examine the spiritual development of children in broken-home families based on the concept of Christian pedagogy. The method used is qualitative with a biographical study approach. Data was taken by interview and observation techniques. The individual who became the research subject was a young girl at a local church in South Sulawesi. The study results show that child's spirituality in broken-home families is less developed. The psychological pressure she felt made her doubt the existence of God and His love for her. This seems to encourage the child to behave negatively and deviate. Against this condition, parties outside the family, such as the church and others, need to pay serious attention by involving them in the process of religious education that can make them feel the existence of God and His sincere and limited love. An empathetic educational process would bring wounded children closer to God and direct them to a better life.